Successful Intra- but Not Inter-species Recombination of msr(D) in Neisseria subflava - de Block, Tessa; González, Natalia; Abdellati, Saïd; Laumen, Jolein Gyonne Elise; Van Dijck, Christophe; De Baetselier, Irith; Van den Bossche, Dorien; Manoharan-Basil, Sheeba S.; Kenyon, Chris (Frontiers in Microbiology, 2022)
Resistance acquisition via natural transformation is a common process in the Neisseria genus. Transformation has played an important role in the emergence of resistance to many antimicrobials in Neisseria gonorrhoeae and Neisseria meningitidis. In a previous study, we found that currently circulating isolates of Neisseria subflava had acquired an msr(D) gene that has been found to result in macrolide resistance in other bacteria but never found in Neisseria species before. To determine if this resistance mechanism is transferable among Neisseria species, we assessed if we could transform the msr(D) gene into other commensal and pathogenic Neisseria under low dose azithromycin pressure. Intraspecies recombination in commensal N. subflava was confirmed with PCR and resulted in high-level macrolide resistance. Whole-genome sequencing of these transformed strains identified the complete uptake of the msr(D) integration fragment. Sequence analysis showed that a large fragment of DNA (5 and 12 kb) was transferred through a single horizontal gene transfer event. Furthermore, uptake of the msr(D) gene had no apparent fitness cost. Interspecies transformation of msr(D) from N. subflava to N. gonorrhoeae was, however, not successful.